Influence of presbyopia on smartphone usage among Chinese adults: A population study. (13th June 2019) - Wang, Congyao; Wang, Xiuqin; Jin, Ling; Tang, Bobby; Zhu, Wenhui; Zhang, Guoshan; Chen, Tingting; McAneney, Helen; Kassalow, Jordan; Congdon, Nathan
Abstract: Importance: Presbyopia, an essentially universal, age‐related loss of the ability to focus un‐aided on near objects, is the world's leading cause of visual impairment. Background: Smartphone use is widespread in China, but little is known about the prevalence, determinants and correction of difficulties with smartphone use in the setting of presbyopia. Design: Cross‐sectional data from a population‐based longitudinal cohort study. Participants: A total of 1817 persons aged ≥35 years in Guangzhou, Southern China. Methods: Participants underwent near visual acuity (NVA) testing and completed questionnaires on smartphone usage detailing knowledge of their own presbyopia status, frequency (hours/day) and subjective difficulties with use of mobile and smartphones. Presbyopia was defined as uncorrected bilateral NVA ≤6/12 with best‐corrected bilateral NVA >6/12. Main Outcome Measures: Difficulty in smartphone use associated with uncorrected presbyopia. Results: Among 1427 respondents (78.5%) undergoing examination, 1191 (83.5%) completed questionnaires (mean age 52.3 ± 11.6 years; 54.9% women). Among 451 persons (37.8%) with presbyopia owning smartphones, 290 (64.3%) reported difficulty using them. Multiple ordinal logistic regression modelling showed difficulty in smartphone use due to presbyopia was associated with higher educational level ( P = .013), worse NVA ( P < .001) and more time spent using smartphones ( P = .002 for 1‐3 hours/day). Among persons with presbyopia owning smartphones, 353 (78.0%) said they would pay >US15 (median US45) for innovations making smartphone use easier. Conclusions and Relevance: Difficulty in using smartphones in the presence of presbyopia is common and affected persons are willing to pay for useful solutions to the problem.